Ketika Aborsi Menjadi Pilihan Analisis Pengambilan Keputusan Dalam Melakukan Aborsi - Rini Rini (Universitas Persada Indonesia YAI, 2022)
Abortion cases are increasing both globally and nationally. What had been the reason forsomeone to think about having an abortion becomes important to research. Theparticipants in this study were 19 women who had an abortion. Accidental Samplingtechnique has been used as the sampling technique while data collection through in-depthinterviews with participants via telephone. Data analysis was carried out with adescriptive qualitative approach. The results of the analysis shows that internal factorsthat influence abortion decision making are personal choices when the pregnancy areeither pregnancy outside of marriage, pregnancy due to infidelity, pregnancy with tooclose distance from the previous pregnancy, the desire to maintain a good name,emotional unpreparedness or personal health. While the external factors are coercionfrom a partner, rape, career, economy and coercion from parents